Optimalisasi Kompetensi Profesional Guru Sekolah Dasar dalam Meningkatkan Partisipasi Belajar Siswa di Kelas - Yudhistira, Santi; Medellu, Gita Irianda Rizkyani (Jendela Akademika, 2024)
The vast shifting of generations became a major adaptation that teachers need to face. The new generation with different characteristics due to environmental influence would challenge the teacher to upgrade their competition to the limit. Therefore, the teacher had to enhance their knowledge and competition in education implementation. This training for teachers is provided using interactive seminars, FGD, and practical methods. All processes were held for two days with different themes but related to each other. Participants showed very high enthusiasm during the activity and shared their own experiences from class. This showed that participants were motivated to find out more about material and cases in their school environment which can be a benchmark for the success of program implementation. This training was the initial activity of the early stages of education and would require a follow-up plan to reduce the realization of activities that can be carried out directly in class with students.